Hauptsache Museum: Der Alte Orient im Fokus. Festschrift für Ralf-B. Wartke - Marzahn, Joachim; Pedde, Friedhelm (Zaphon, 2018)
Anderthalb Dutzend Beiträge zur Archäologie des Antiken Vorderen Orients, Südarabiens und Äthiopiens sind Ralf-B. Wartke, langjährigem Kustos am Vorderasiatischen Museum in Berlin, gewidmet. Artikel zur bislang unpublizierten Funden und zur Neubewertung bereits bekannter Funde werden ergänzt um wissenschaftshistorische Beiträge. One and a half dozen contributions are devoted to the archaeology of the Ancient Near East, including Old South Arabia and Ethiopia. They are dedicated to Ralf-B. Wartke, custodian of the Vorderasiatisches Museum in Berlin. Several studies focus on statues and figurines, others present revaluations of published and hitherto unpublished objects. These are supplemented by studies on the history of ANE scholarship and the impact of ANE architecture on 20th century architecture. Reihe E009677400 - Band 6